Keanekaragaman Jenis Burung di Hutan Adat Sub Suku Afsya, Kampung Bariat Distrik Konda Kabupaten Sorong Selatan Provinsi Papua Barat Daya - Purba, Fitri Dewi Handayani Br; Irwanto, Irwanto; Pattinasarany, Cornelis Karel (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2026)
The customary forest of Sub-Tribe Afsya, Bariat Village, South Sorong Regency, Southwest Papua is a lowland tropical rainforest of approximately 2,500 hectares managed under the indigenous "Sasi Adat" system. This study aimed to determine bird species diversity, evenness of distribution, and the relationship between bird communities and vegetation structure. Research was conducted in January 2026 using a combination of line transect and point count methods along five 1,000-meter transects, observed in the morning (06:00–10:00 WIT) and afternoon (15:30–18:00 WIT). Data were analyzed using the Shannon–Wiener Diversity Index (H’), Simpson's Dominance Index (D), Evenness Index (E), and vegetation Important Value Index (IVI). The study recorded 30 bird species from 16 families with 492 individuals, including 12 Papua-endemic species protected under Minister of Environment and Forestry Regulation No. P.106/2018. H’ values ranged from 1.197 to 2.472 (moderate to high); dominance was low to moderate; and evenness ranged from 0.668 to 0.933, with most transects showing high evenness (E > 0.75). Vegetation was dominated by damar trees (Agathis labillardierei) and fruiting trees synergistically supporting frugivore, insectivore, and nectarivore bird guilds. The Sasi Adat management system demonstrably contributes to habitat quality, rendering this forest of significant conservation value for Southwest Papua's avifauna.